The Role of Digital Literacy in Reducing Disinformation in the Social Media Era - Saputro, Wahyu Eko (Worldwide Research Publishing, 2025)
The development of social media in Indonesia has massively increased access to public information, but it also presents a serious challenge in the form of disinformation that has the potential to undermine social cohesion and democracy. Digital literacy is seen as a strategic ability that can protect the public from exposure to false information. This study aims to analyze the role of digital literacy in reducing people's vulnerability to disinformation on social media, focusing on identifying the level of digital literacy, the relationship between digital literacy and disinformation vulnerability, and strategies to increase digital literacy. This study uses a quantitative approach with an explanatory survey design. A sample of 400 respondents was determined through purposive sampling with the criteria of active social media users. The research instrument is in the form of an online questionnaire that measures the dimensions of digital literacy and vulnerability to disinformation. Data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. The results showed that most respondents were in the